2020
DOI: 10.1016/j.neurobiolaging.2019.10.004
|View full text |Cite
|
Sign up to set email alerts
|

EEG spectral power abnormalities and their relationship with cognitive dysfunction in patients with Alzheimer's disease and type 2 diabetes

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 138 publications
8
42
0
Order By: Relevance
“…Despite the lack of clear neurophysiological markers, there is a strong epidemiologic bond between diabetes and the development of dementia, possibly related to glycemic control and insulin dysregulation [ 20 , 21 ]. Recent work shows similar cortical plasticity patterns between T2DM, cognitive function and Alzheimer’s Disease (AD), including abnormal long-term potentiation (LTP)-like plasticity mechanisms and Glutamatergic neurotransmission inferred by TMS studies [ 43 , 44 ] and diffuse oscillatory activity slowing reflected by shifts from higher to lower frequencies in EEG power analysis [ 45 ]. Also, a subset of the ACCORD-MIND RCT trial showed that an increase of 1% in HbA 1c levels was associated with lower cognitive and memory test scores [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of clear neurophysiological markers, there is a strong epidemiologic bond between diabetes and the development of dementia, possibly related to glycemic control and insulin dysregulation [ 20 , 21 ]. Recent work shows similar cortical plasticity patterns between T2DM, cognitive function and Alzheimer’s Disease (AD), including abnormal long-term potentiation (LTP)-like plasticity mechanisms and Glutamatergic neurotransmission inferred by TMS studies [ 43 , 44 ] and diffuse oscillatory activity slowing reflected by shifts from higher to lower frequencies in EEG power analysis [ 45 ]. Also, a subset of the ACCORD-MIND RCT trial showed that an increase of 1% in HbA 1c levels was associated with lower cognitive and memory test scores [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In view of increasing life expectancy [16], NFT could improve the social well-being of the growing elderly population in the future. Previous classical NFT studies on healthy young adults showed significant changes in theta (4-8 Hz) [17,18], alpha (8)(9)(10)(11)(12)(13) Hz) [19][20][21], and beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) [21] band powers. These studies also reported significant improvements in the results of neuropsychological tests for the assessment of memory-related [17,19,21], attention [17,21], and visuospatial functions [20].…”
Section: Introductionmentioning
confidence: 87%
“…The RP measurement gives information on the normalized weight of each band in the spectral distribution. The spectral bands selected to assess the induced EEG changes were delta (0.1-4 Hz), theta (4-8 Hz), alpha (8-13 Hz), and beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). The lower (l f i ) and upper (u f i ) frequency limits of each band were specified according to the classical definitions of EEG bands [57].…”
Section: Relative Powermentioning
confidence: 99%
“…Issues regarding mental disorders are still of interest to scholars (e.g., [270][271][272][273][274][275][276][277]), in particular, epilepsy, Alzheimer's disease, mild cognitive impairments, synchronization, and attention-deficit/hyperactivity disorders. For epilepsy, recent research is concerned with issues such as proposing a deep learning-driven EEG approach to detect epileptic seizures from EEG discharges [278], epilepsy lateralization through intra-hemispheric brain networks based on resting-state magnetoencephalography data [279], and EEG-based multiclass seizure type classification using CNNs and transfer learning [280].…”
Section: Latest Research Concerning Ai-enhanced Eeg Analysismentioning
confidence: 99%